2022
DOI: 10.5483/bmbrep.2022.55.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Translocalization of enhanced PKM2 protein into the nucleus induced by cancer upregulated gene 2 confers cancer stem cell-like phenotypes

Abstract: Increased mRNA levels of cancer upregulated gene (CUG)2 have been detected in many different tumor tissues using Affymetrix microarray. Oncogenic capability of the CUG2 gene has been further reported. However, the mechanism by which CUG2 overexpression promotes cancer stem cell (CSC)-like phenotypes remains unknown. With recent studies showing that pyruvate kinase muscle 2 (PKM2) is overexpressed in clinical tissues from gastric, lung, and cervical cancer patients, we hypothesized that PKM2 might play an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Using microRNA microarrays, Yawut (26) discovered that overexpression of CENPW reduced the levels of miR-3656, leading to upregulation of JMJD5, ultimately leading to a cancer stem cell-like phenotype (CSC). Another study demonstrated that CENPW-induced increased nuclear pyruvate kinase muscle 2 (PKM2) expression, promoting a CSC-like phenotype by upregulating c-Myc and CyclinD1 as co-activators (27). Additionally, CENPW enhances cancer cell metastasis and drug resistance by activating signal transducer and activator of transcription 1 in colon cancer, ultimately promoting tumor progression (28).…”
Section: Discussionmentioning
confidence: 99%
“…Using microRNA microarrays, Yawut (26) discovered that overexpression of CENPW reduced the levels of miR-3656, leading to upregulation of JMJD5, ultimately leading to a cancer stem cell-like phenotype (CSC). Another study demonstrated that CENPW-induced increased nuclear pyruvate kinase muscle 2 (PKM2) expression, promoting a CSC-like phenotype by upregulating c-Myc and CyclinD1 as co-activators (27). Additionally, CENPW enhances cancer cell metastasis and drug resistance by activating signal transducer and activator of transcription 1 in colon cancer, ultimately promoting tumor progression (28).…”
Section: Discussionmentioning
confidence: 99%